IMPLANTACIÓN DE LA CONTABILIDAD COMERCIAL Y APLICACIÓN DE INDICADORES FINANCIEROS EN LA FARMACIA ALEXANDRA DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA, EN EL PERÍODO 1 DE JULIO AL 31 DE DICIEMBRE DEL 2013 - Ramirez Alvarado, Katerine Johanna (2016)
This thesis entitled "IMPLEMENTATION OF THE COMMERCIAL APPLICATION OF ACCOUNTING AND FINANCIAL INDICATORS IN THE ALEXANDRA PHARMACY, CATAMAYO, PROVINCE OF LOJA IN THE PERIOD JULY 1 TO DECEMBER 31, 2013", was developed in order to implement a system commercial accounting under International Accounting Standards (IAS), consistent with the economic activities of the pharmacy in this course of six months, by which real and timely information is obtained to provide a significant contribution to the owner of Pharmacy Alexandra with which you can make sound decisions in the administration of it. The goals they have set for the completion of this work, mention the design of accounting records to monitor and record the economic activities of Pharmacy; and subsidiary records such as purchase and sales assistant capable of recording detailed analytically and purchases and sales by the Pharmaceuticals and thus maintain proper inventory control and cash is handled, likewise the auxiliary accounts charge which serves to control credit sales made to customers and where the date and amount of the sale made is recorded; the auxiliary accounts payable whose function is to break down the movement of credits and debits from suppliers; preparing the book that allowed banks to control the movement of money as deposits, withdrawals and paid by checks drawn by the Bank; we proceeded to develop the plan and operating accounts, according to the economic activity of the pharmacy as well as the economic movement of the same, physical 6 verification of assets, stocks and bonds that owns the pharmacy to determine the initial inventory was conducted and determine the balance, which has been handled through the Multiple System has yielded information on the physical quantity of existing pharmaceuticals and meet the cost of goods sold and therefore the profit obtained. With this information we were able to get to the initial situation, in which detailed, values, assets and liabilities with those who started to work, the record of activities in the daily paper, up to get financial statements summarizing both economic and financial activity of the pharmacy, first the State Economic Situation where casts a net profit of $ 8.917,64; and the Statement of Financial Position reflecting a value of $ 117.633,57 assets, liabilities and assets 11.864,99 worth $ 10.768,58. By using financial indicators in line with its economic movement, allowed interpretations deduced by the degree of liquidity that owns the pharmacy which is 6,50 amount sufficient to cover short-term debt therefore has sufficient cash resources to conduct its business ; with indicators of activity, it was determined that inventories rotate slowly due to excess merchandise that has not control loans granted to its customers and is not canceled by the deadline debts to its suppliers is made, regarding profitability indicators was determined that the return on sales is 26.91% and return on equity 8.43%, values that are stable, but still low.